Chondroitin Sulfates Control Invasiveness of the Basal-Like Breast Cancer Cell Line MDA-MB-231 Through ROR1 - Nadanaka, Satomi; Tamura, Jun-ichi; Kitagawa, Hiroshi (Frontiers in Oncology, 2022)
Extracellular and cell surface chondroitin sulfates (CSs) regulate cancer cell properties, including proliferation and invasion. Thus, it is necessary to understand the mechanisms underlying their roles in cancer. Although we have shown that CS has an inherent ability to enhance the invasive activity of the human triple-negative breast cancer cell line MDA-MB-231, its molecular mechanism remains elusive. Here, we focused on receptor tyrosine kinase-like orphan receptor 1 (ROR1) and dickkopf WNT signaling pathway inhibitor 1 (DKK1). MDA-MB-231 cells express high levels of ROR1; their invasive potential depends on ROR1 signaling. Although accumulating evidence has demonstrated that ROR1 is associated with aggressive breast-cancer phenotypes, the whole picture of its biological function remains poorly understood. In this study, we examined whether CS controls ROR1 function. Surface plasmon resonance analysis indicated that CSs were bound to ROR1 in the presence of WNT5A. The invasive activity of MDA-MB-231 cells enhanced by CSs was completely suppressed by ROR1 knockdown. In addition, knockdown of the CS biosynthetic enzymes CHST11 and CHST15 inhibited invasive activity, even in the presence of ROR1. These results suggest that CS is required to induce an ROR1-dependent, aggressive MDA-MB-231 phenotype. ROR1 signaling in MDA-MB-231 cells activated c-Jun N-terminal kinase (JNK), leading to increased invasive potential; moreover, exogenous CSs activated JNK. MDA-MB-231 cells express DKK1, a tumor suppressor factor that binds to CS, at high levels. Knockdown of DKK1 enhanced CS-stimulated tumor invasion activity of MDA-MB-231 cells, suggesting that DKK1 sequesters CS to block ROR1/JNK signaling. These results showed that CSs promotes cancer aggressiveness through the ROR1JNK axis in MDA-MB-231 cells.